Fishermen's perception and the estuarine set bag net fishery in Bangladesh - Md. Rashed-Un-Nabi; Md. Azharul Hoque; Ridzwan Abdul Rahman; Saleem Mustafa; Md. Abdul Kader (International Journal of Rural Studies (IJRS), 2006)
A five point Likert scale was developed to study fishermen’s perception of the Estuarine Set bag Net (ESBN) fishery of Bangladesh. Twenty five scalable questions with their probable answers were identified and ranked through focused group discussion with the fishermen and the key informant of the villages investigated. Every question was treated as an attribute or variable. These attributes were broadly categorized into five composite attributes: (i) present management status, (ii) bio-diversity, (iii) social structure, (iv) economic condition and (v) present occupational satisfaction. The combined mean value (4.46) for all variables, the means of the composite attributes and individual mean values for each variable were found significant at 5% level of significance. The highest mean (4.88) was observed for the variable “Have you ever been encouraged to practice community management system for ESBN fishery?” while the minimum mean value (3.61) was found for the variable “Which species would you prefer for commercial purposes?” For composite attributes, the highest mean (4.64) was observed for “Present occupational satisfaction” while the lowest (4.11) was found for “Bio-diversity”. Seven components were extracted which altogether explained 60.86% of the total variance of all 24 variables included in the data set. The first, second, third and fourth components were found highly correlated with the variables included in the composite attributes “Bio-diversity”, “Economic Condition”, “Social Structure” and “Present Management System” respectively. The fifth and sixth components were found highly correlated with the variables associated with the composite attribute “Present Occupational Satisfaction”.